Efficacy of hyperbaric oxygen therapy in treating sudden sensorineural hearing loss: an umbrella review - Liu, Xinghong; Xu, Xianpeng; Lei, Qiulian; Jin, Xiaohua; Deng, Xinxing; Xie, Hui (Frontiers in Neurology, 2024)
Intr oduction:Our objective was to explore the efficacy of hyperbaric oxygen in the treatment of sudden sensorineural hearing loss by conducting an umbrella review of all existing evidence. Methods:We conducted an umbrella review, searching for related articles in the PubMed, Web of Science, Embase, and Scopus databases. The search period covered from the inception of each database until April 2024.We extracted authors, country of publication, time of publication, number of included studies and participants, interventions, summary of results, p-values, I², relative risk (95% CI), and outcome measures. The methodological quality, evidence quality, and overlap rate of the included articles were assessed using AMSTAR 2, GRADE, and OVErviews (GROOVE).Results:Methodological quality was assessed using AMSTAR 2. Of the 9 included articles, 2 were assessed as "high", 3 as "moderate", 2 as "low", and the remaining 2 as "very low". The quality of evidence was assessed using the GRADE system. It was found that the quality of evidence in most of the studies was unsatisfactory. It was found that there was a slight overlap among the included articles. 6 studies reported positive results (OR 1.37; 95% CI, 1.17-1.61; P=0.04), with high heterogeneity observed (I2=63%). Egger's test indicated bias (P=0.000101). 3 studies reported negative results (MD 1.49; 95% CI, -0.32-3.29; P=0.43; I2=0%), with no significant bias detected (P=0.106) according to Egger's test.Conclusion:HBO therapy is shown to be an effective treatment for SSNHL with fewer side effects. However, the methodological quality and evidence of the systematic reviews and meta-analysis included in this study were generally low. Therefore, more high-quality, large-scale, multi-center randomized controlled trials are needed in the future to verify the efficacy of HBO therapy for SSNHL.